N-p-Toluenesulfinylimidazole: A New in situ Reagent for the Mild and Efficient Synthesis of p-Toluenesulfinate Alkyl Esters and Aryl Esters - Shaw, Jessica L.; Austermuehle, Brad J.; Witte, Jordan M.; Dorsey, Timothy R.; Delach, Christina; Hamaker, Christopher G.; Hitchcock, Shawn R. (Synthesis, 2021)
A new synthetic methodology has been developed for the synthesis of sulfinate alkyl and aryl esters. The methodology involves the combination of p-toluenesulfinic acid and 1,1′-carbonyldiimidazole (CDI) to create the putative reagent sulfinylimidazole. The process spontaneously releases carbon dioxide upon the addition of the CDI to the acid suggesting the rapid formation of the proposed reagent. Reaction of this reagent with a series of alcohols (primary, secondary, and tertiary) afforded the corresponding sulfinate alkyl esters in good to excellent yields by the addition of alcohols. It was also possible to form the related sulfinate aryl esters by treating the proposed sulfinylimidazole with selected phenols (phenol, p-tert-butylphenol, and thymol). The aryl esters were formed in excellent conversion based on analysis of the 500 MHz 1H NMR spectra of the crude reaction mixtures.
Keywords: sulfinate ester; sulfinate aryl ester; p-toluenesulfinic acid; 1,1′-carbonyldiimidazole; sulfinylimidazole